Positividad y negatividad del aburrimiento: una hermenéutica de la cotidianidad - Dasuky Quiceno, Samir Ahmed; Galvis Mejía, Juan Pablo (Pontificia Universidad Católica del Perú. Departamento de Humanidades, 2023)
This paper considers the positivity and negativity of boredom to understand the horizon in which contemporary society constructs its sense of everyday life. Mymethod follows Heidegger’s interpretative proposal, guided by the concept of everyday life in dialogue with Han, concerning the manifestation of boredom inthe everyday life of individuals. In the first part of this paper, I discuss the determinations of instrumental rationality and neoliberalism in sense-constructionwithin contemporary society. Then, in the second part, I attempt to explain the dialectic impossibility of the positivity of boredom. This leads to understanding how the negativity of boredom enables from dialectics a negation of neoliberal discourse. Understanding this is relevant when positing the negativity of boredom as a world possibility. I conclude that boredom is an openness to the ways in which contemporary society constructs its everyday life.

En el presente artículo se pretende comprender el horizonte en el que la sociedad contemporánea construye su sentido de la cotidianidad, a partir de lapositividad y negatividad del aburrimiento. El método empleado será la propuesta interpretativa de Heidegger, orientado por el concepto de cotidianidad en dialogo con Han, en lo referente a la manifestación del aburrimiento en la vida cotidiana de los sujetos. En una primera instancia se abordan las determinaciones de la racionalidad instrumental y el neoliberalismo en la construcción de sentido en la de la sociedad contemporánea. Posteriormente, en un segundo lugar, se comprende la imposibilidad dialéctica de la positividad del aburrimiento, para luego entender cómo la negatividad del aburrimiento posibilita desde la dialéctica una negación del discurso neoliberal. Esta comprensión resulta relevante al momento de plantear la negatividad del aburrimiento como una posibilidad de mundo. Se concluye, que el aburrimiento es una apertura a los modos en los que la sociedad contemporánea construye su cotidianidad.
Positivity and Negativity of Boredom: A Hermeneutic of Everyday Life
Keywords: Everyday life; Neoliberalism; World possibility; Instrumental rationality; Dasein; Contemporaneidad; Neoliberalismo; Posibilidad de mundo; Racionalidad instrumental; Dasein; https://purl.org/pe-repo/ocde/ford#6.03.01